POLÍTICAS PÚBLICAS DE INCENTIVOS E FINANCIAMENTOS PARA PESQUISA E INOVAÇÃO NA AGRICULTURA EM FUNDAÇÕES DE PESQUISAS - Galvan, Walter (2018)
Due to technological and organizational innovation, Brazilian agriculture is increasingly consolidating as one of the world's leading food producers. The major challenge of this sector is to meet global demand for food, which according to FAO - Food and Agriculture Organization in 2050 will be 60% higher than today. This challenge is aggravated by changes in dietary habits, climate change and environmental impacts. It is therefore necessary to invest in agriculture research. Nowadays, investments are concentrated in the private sector and the public sector mainly participates in tax incentives and some subsidized credit lines. For this study, Resource Based Theory was used as the groundwork, which assumes that no organization is able to generate all the resources it needs for its survival and growth, and depend on its external environment for obtaining resources that enable its operation. Accordingly the general objective was to discuss the participation of the public policies of incentives and financing for research and innovation in agriculture in five Research Foundations in the southern region of Brazil. The study was descriptive and comparative, with a qualitative approach. For data collection, semi-structured interviews were conducted with the managers responsible for the five selected Research Foundations. Using the content analysis technique, the data were analyzed and interpreted from three categories of analysis: a) relevant cost factors; b) factors relevant to knowledge; c) infrastructure and innovation products. The results pointed out that, despite the existence of financing lines and fiscal incentives, there is still a predominance of private resources in conducting research for innovation in agriculture. The studied Research Foundations rely on maintainers, who are responsible for providing resources not coming from the public sector or from the entity organic revenues. As a practical contribution, this study allows us to better understand the reality of the Research Foundations so that public policies to encourage research and innovation in agriculture become effective and generate benefits for the country